Recurrent Hidradenocarcinoma in the Abdominal Wall with no Distant Metastasis: A Case Report and Literature Review - Yahia Hameed Al-Ani; Raid M. Al-Ani; Wassan Nori; Israa Mahdi Al-Sudani (Diyala Journal of Medicine)
Background: Hidradenocarcinoma is a rare, aggressive tumor with a high rate of local recurrence and distant metastasis. There are no current management guidelines, and surgery has been used to control the primary disease. Even with wide surgical excision, the course of the tumor is unpredictable, and the prognosis for survival is poor. The most common location is the scalp, followed by the extremities, and rarely the trunk.